Adult learner strategies in foreign language grammar learning: a task-based study of approaches to the learning of grammatical structure in a micro-language, with a discussion of their implications for language teaching and materials - Ryan, Althea (University of Edinburgh, 1986)
This study sets out to explore adult learner strategies in foreign language learning. It takes its point of departure in theories about cognitive styles and learning strategies, even though such theories have been developed mainly on the basis of studies of learner performance in tasks whose contents are less skill-oriented than FLL. A particular both theoretical and methodological inspiration has been found in the approach of Pask and his associates. It is a major hypothesis that a learner's choice of strategy in an FLL task will depend not only an the nature of the task but also on individual learner preferences. The empirical basis of the study is a record of the activities of 33 adult subjects performing the task of learning a micro-language in an environment that allows them choice of approach. The number of subjects and the size of the task do not permit conclusions of statistical significance, but the task does lead to the establishment of differences in learning strategy, which the author calls Rules-based and Examples-based learning. The further exploration of these is bound to contribute to an elucidation of the FLL process. The author sees the most important perspectives of the study in the development of teaching materials and in lesson design. The findings support suggestions as to far-reaching changes in the design of grammar presentation material and pedagogic grammars, and in the use of text examples in teaching. They also support a revision of present practice with regard to principles for content syllabus organization, and to the selection of materials for certain types of language learning activity, especially reinforcement activity. The suggestions are made on the assumption that in so far as learners can be seen to vary in preferred learning strategy, their learning cannot but be furthered by teaching designs that allow them to indulge their preference.
Keywords: Linguistics